2019
DOI: 10.1080/21645515.2019.1638203
|View full text |Cite
|
Sign up to set email alerts
|

Do previously held vaccine attitudes dictate the extent and influence of vaccine information-seeking behavior during pregnancy?

Abstract: Pregnancy represents a high information need state, where uncertainty around medical intervention is common. As such, the pertussis vaccination given during pregnancy presents a unique opportunity to study the interaction between vaccine attitudes and vaccine information-seeking behavior. We surveyed a sample of pregnant women (N = 182) during early pregnancy and again during late pregnancy. The variables of vaccine confidence and risk perception of vaccination during pregnancy were measured across two questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 52 publications
(61 reference statements)
1
20
0
Order By: Relevance
“…Interestingly, we found that mothers who took the vaccine based on their own personal decision had both excellent knowledge and positive attitude towards the vaccine. This pattern was also observed in a study conducted by Clarke et al which found that (68%) of pregnant women were not influenced by family or friends when making the decision to be vaccinated [15]. Participants in this study did not rely greatly on information gained from their family and friends, this could be a reflection of their trust in the validity of the information provided by the Ministry of Health.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, we found that mothers who took the vaccine based on their own personal decision had both excellent knowledge and positive attitude towards the vaccine. This pattern was also observed in a study conducted by Clarke et al which found that (68%) of pregnant women were not influenced by family or friends when making the decision to be vaccinated [15]. Participants in this study did not rely greatly on information gained from their family and friends, this could be a reflection of their trust in the validity of the information provided by the Ministry of Health.…”
Section: Discussionsupporting
confidence: 81%
“…When faced with a decision to vaccinate, it is common to seek more information -particularly during pregnancy when information-seeking behaviours are heightened [27]. The reported lack of vaccine information from HCPs paired with a heavy use of the internet for maternal health information is an issue of concern [28]. Facebook and Google, both widely cited by study participants as key information sources, have been previously studied for their potential to propagate vaccine misinformation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Participants mentioned con icting advice about the Covid vaccination as a particular challenge in this respect. Similarly, several studies have shown that pregnant women experience a wealth of contradictory opinions and guidance about other vaccination programmes during pregnancy (47)(48)(49). This inconsistency may be problematic if women choose to trust information from their social network over information from health professions, with potentially severe consequences for both the mother and child's health.…”
Section: Discussionmentioning
confidence: 99%